(untitled) (Medical Forum Monthly, 2024)
Objective: To assess lack of antenatal visits as a reason of Primary Cesarean-Section in multi-parous women with previous S.V.D. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Department of Community Medicine, Jinnah Postgraduate Medical Centre, Civil hospital and Sobraj Hospital, Karachi from May to August 2017. Materials and Methods: A study was conducted on a sample of 130 women (undergone Primary cesarean section with previous S.V.D) taken through non probability purposive sampling from 3 hospitals of Karachi namely, Jinnah Postgraduate Medical Centre, Civil hospital and Sobraj hospital. A structured self-administered questionnaire was developed. An informed verbal consent was taken and a pilot study was conducted to assess the validity of the questionnaire. The questionnaire was then distributed, got filled, data was analyzed using SSPS version 16.0, with 95% confidence interval and 0.05 p-value as statistically significant. Results: Out of the 130 primary caesarean deliveries during the study period 35.4% were indicated for mal-presentation, 25.4% for antepartum hemorrhage 20.0% for fetal distress, and 16.2% for pre-eclampsia. 73.8% (p-value= 0.035) patients had hypertension during pregnancy. When asked if these patients experienced any swelling in the hands or feet’s during that time, a total number of 49.2% (p-value= 0.04) complained they had. 70.8% (p-value= 0.023) patients gave the history of fits during pregnancy. Antenatal clinics were frequented by only a mere 40.8% (p-value=0.005) of the patients. Among these 130 patients, reduced fetal movements were felt by 54.6% (p-value= 0.006) of the total consensus. A total of 52.3% (p-value= 0.00) were informed by their health worker about the abnormal position of their baby. It was also noted that 53.1 % (p-value= 0.00) of the patients were told by their doctor that they have a low lying placenta, and 56.9% (p-value= 0.00) of the total had an episode of severe vaginal bleeding at any time of pregnancy. Conclusion: Previous vaginal delivery gives the family and the doctors a false sense of security that overshadows the need for vigilant antenatal and intra-partum care. The method of previous deliveries shouldn’t be the primary criteria upon which the current delivery is decided. Rather, every pregnancy should be treated with as much concern and care as the first. (The physicians should display obligation in such circumstances and assess the pregnancy thoroughly before heading towards a massive scheme. Rather than promoting the doctors’ own interests and convenience, Mothers’ health and wellbeing should be considered the first priority and every possible measures should be taken to ensure that. The antenatal care should be the utmost preference and necessary investigations should be practiced. WHO recommends a minimum of four antenatal visits, comprising interventions such as tetanus toxoid vaccination, screening and treatment for infections, and identification of warning signs during pregnancy? With all the adequate steps taken, the rate and reasons of cesarean sections could be monitored and restricted hence progressing to initiate a huge stride for maternal and fetal health.